Efektifitas Model Pembelajaran Kooperatif Tipe Scramble Dalam Pembelajaran Matematika - Iltavia Iltavia; Nurhasnah Nurhasnah (Jurnal Ilmiah Pendidikan Scholastic, 2019)
The problem formulation in this study is 1). How is the teacher's activity in the application of a scramble type cooperative learning model on Mathematics learning in class XI SMK Cendana Padangpanjang 2017/2018 Academic Year? 2). How is the activity of students in the application of scramble type cooperative learning models in mathematics learning in class XI SMK Cendana Padangpanjang class year 2017/2018, 3). Are students' mathematics learning outcomes using a scramble type cooperative model on effective mathematics learning to improve mathematics learning outcomes in the cognitive domain? To test the validity of the hypothesis the pretest and posttest values were analyzed using the t-test. Obtained then rejected and be accepted . This has the effect of increasing the percentage of good completeness as much as 75% of the mathematics learning outcomes. From the results of data analysis it can be concluded that by applying the Scramble Type Cooperative learning model has a good effect on students' mathematics learning outcomes in class XI TKJ SMK Cendana Padangpanjang